Effects of neem (Azadirachta indica) on fecundity hatchability and survivality of snails (Lymnea acuminata) - Singh, K. (Gorakhpur Univ., Gorakhpur (India). Dept. of Zoology) (2013)
The effect of neem oil, Nimbecicine, Achook and pure Azadirachtin on the fecundity, hatchability of the snail Lymnaea acuminata, and the survival of young snails were studied. It was observed that neem based products significantly caused time dependent reduction in fecundity, hatchability and survival of young snails. Maximum effect was observed in pure Azadirachtin exposed snails